Evaluation methods of clay stabilizer in shale reservoirs based on X-ray diffraction and capillary suction time - HE Yanlong; WANG Xin; XUE Xiaojia; HUANG Hai; WU Jiang; LIU Xiaoqing; TANG Siyuan; HU Zhiqiang (Youqi dizhi yu caishoulu)
The differential evaluation of fracturing fluid and its additives is an important link in the integrated development process of shale reservoir engineering geology， and clay stabilizer is a crucial additive. Therefore， the rapid screening of clay stabilizers plays an important role in protecting shale reservoirs and ensuring fracturing effects. By introducing the detection method of capillary suction time （CST） and combining it with the mineral composition of core samples obtained by X-ray diffraction， the calculated CST of core samples from shale reservoirs was obtained by weighting. The correlation between the detected and calculated CST of core samples and the calculated and detected cation exchange capacity （CEC） obtained by the traditional clay stabilizer evaluation method was established， respectively. It was found that they all had the same changing trend as the detected CEC. By introducing the proportional coefficient， the detected and calculated CST was fitted with the calculated CEC， and the corresponding fitted detection value of CEC was obtained. The relative errors between them and detected CEC were analyzed， respectively， and it was found that the average relative errors were all less than 5%. The experimental results show that both the detected CST of core samples and the calculated CST based on X-ray diffraction and standard mineral CST detection value can be used to evaluate and screen clay stabilizers. Compared with the traditional CEC evaluation method， the CST detection method is rapid and accurate and is suitable for the complex clay mineral composition and strong heterogeneity of shale reservoirs.